Self-Generated Gradients Yield Exceptionally Robust Steering Cues - Tweedy, Luke; Insall, Robert H. (Frontiers in Cell and Developmental Biology, 2020)
Chemotaxis is a widespread mechanism that allows migrating cells to steer to where they are needed. Attractant gradients may be imposed by external sources, or self-generated, when cells create their own steep local gradients by breaking down a prevalent, broadly-distributed attractant. Here we show that chemotaxis works far more robustly towards self-generated gradients. Cells can only respond efficiently to a restricted range of attractant concentrations; if attractants are too dilute, their gradients are too shallow for cells to sense, but if they are too high, all receptors become saturated and cells cannot perceive spatial differences. Self-generated gradients are robust because cells maintain the attractant at optimal concentrations. A wave can recruit varying numbers of steered cells, and cells can take time to break down attractant before starting to migrate. Self-generated gradients can therefore operate over a greater range of attractant concentrations, larger distances, and longer times than imposed gradients. The robustness is further enhanced at low cell numbers if attractants also act as mitogens, and at high attractant concentrations if the enzymes that break down attractants are themselves induced by constant attractant levels.